2010
DOI: 10.1159/000314038
|View full text |Cite
|
Sign up to set email alerts
|

Feticide Followed by Mifepristone-Misoprostol Regimen for Midtrimester Termination of Pregnancy in Two Cases of Complete Placenta Previa

Abstract: Placenta previa (PP), with a frequency of 5–7% in the second trimester, is considered one of the most important causes of obstetric hemorrhage. Surgical curettage is the classically recommended method to perform a midtrimester termination of pregnancy (TOP) in the presence of PP. Recent clinical reports suggest that induction of delivery is possible in these cases, but no information on mifepristone-misoprostol regimen is available. We present 2 cases of mifepristone-misoprostol midtrimester TOP with a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The blood supply to the placenta is an important factor in intrapartum hemorrhage. 2,13 Some research groups have recently suggested that a decrease in the uteroplacental blood flow, such as that caused by preinduction feticide or UAE, may reduce the risk of maternal hemorrhage. 8,14 UAE is widely used in patients with various gynecologic and obstetric conditions, such as postpartum hemorrhage and cesarean scar pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The blood supply to the placenta is an important factor in intrapartum hemorrhage. 2,13 Some research groups have recently suggested that a decrease in the uteroplacental blood flow, such as that caused by preinduction feticide or UAE, may reduce the risk of maternal hemorrhage. 8,14 UAE is widely used in patients with various gynecologic and obstetric conditions, such as postpartum hemorrhage and cesarean scar pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In women with complete placenta previa, there have been several reports about therapeutic termination by vaginal delivery (Table 1) [1][2][3][4][5][6][7][8], but uncontrollable hemorrhage is the greatest risk when vaginal delivery is attempted [2,5,8]. Some authors have reported that performing feticide before induction of labor is effective for decreasing blood loss in women with complete placenta previa [2][3][4][5], but there have also been reports of uncontrollable hemorrhage after feticide or IUFD [5,8]. A laminaria tent or mifepristone is often used to promote cervical ripening [1, 2, 4-6, 8], but the authors could not have used mifepristone because it is not approved in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section is generally required for delivery in patients with complete placenta previa. However, there have been several reports about therapeutic termination by vaginal delivery despite the presence of complete placenta previa (Table 1) [1][2][3][4][5][6][7][8]. When vaginal delivery is attempted in patients with complete placenta previa, uncontrollable hemorrhage is the greatest risk [2,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we performed a PubMed search using the key words “placenta previa” and “termination,” “abortion,” “second trimester,” or “accreta” and excluded “fetal death.” The search was limited to the English literature between 1990 and 2014, from 12 to 23 weeks of gestation, and led to 11 reports, which are summarized in Table 1 . 13 14 15 16 17 18 19 20 21 22 23 …”
Section: Discussionmentioning
confidence: 99%
“…A similar report was published concerning mifepristone- and misoprostol-induced midtrimester TOP with preinduction feticide in patients with a diagnosis of complete placenta previa. 22 They concluded that feticide effectively decreases placenta previa-related bleeding during medical midtrimester TOP. However, these studies investigated small numbers of patients, and further investigation is needed to reveal the usefulness of feticide before the induction of labor.…”
Section: Discussionmentioning
confidence: 99%